Development of functional literacy of schoolchildren: an urgent problem of modern education - Yermekova, Жадыра; Myrzagereikyzy, Гүлмайдан; Serikbayeva, Фариза (Рroblems of engineering and professional education, 2025)
The main way to form a competitive personality is to comprehensively improve the content of subject knowledge and teaching methods at each stage of the education system. This improvement should be aimed at developing students' creative thinking, functional literacy, and life skills. In addition, the content and methods of education should be adapted to modern requirements and adapted to the individual abilities and interests of students. Functional literacy evaluates the results of cognitive abilities and practical actions of students as an indicator of their level of knowledge. This indicator is determined by the effective application of knowledge acquired at school when performing tasks in various life situations, and the applied significance of the acquired knowledge. This article provides an overview of the concept of functional literacy from the works of foreign and domestic scientists, analyzes the level of training of physics teachers in secondary education institutions in the country for the development of functional literacy of students. Also, to study the problem of developing students' functional literacy in physics, a survey of physics teachers from educational institutions in Astana and Atyrau was conducted, pedagogical positions and methodological approaches in this area were studied. Based on these studies, case studies related to life situations were compiled using methods of integrating physics with other disciplines.